2017
DOI: 10.1007/s13361-017-1850-5
|View full text |Cite
|
Sign up to set email alerts
|

Simple Approach for De Novo Structural Identification of Mannose Trisaccharides

Abstract: Oligosaccharides have diverse functions in biological systems. However, the structural determination of oligosaccharides remains difficult and has created a bottleneck in carbohydrate research. In this study, a new approach for the de novo structural determination of underivatized oligosaccharides is demonstrated. A low-energy collision-induced dissociation (CID) of sodium ion adducts was used to facilitate the cleavage of desired chemical bonds during the dissociation. The selection of fragments for the subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 32 publications
0
66
1
Order By: Relevance
“…In this study, the CID spectrum of each disaccharide anomer was measured immediately after the separation of anomers by HPLC. Our previous study on hexose disaccharide sodium adducts demonstrated that both the anomeric configurations of the glycosidic bond and the sugar at the reducing end could be determined by using the relative intensities of glycosidic bond cleavage, dehydration, and cross‐ring dissociation . We ascertained that a similar concept could be applied to hexose disaccharide lithium adducts.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In this study, the CID spectrum of each disaccharide anomer was measured immediately after the separation of anomers by HPLC. Our previous study on hexose disaccharide sodium adducts demonstrated that both the anomeric configurations of the glycosidic bond and the sugar at the reducing end could be determined by using the relative intensities of glycosidic bond cleavage, dehydration, and cross‐ring dissociation . We ascertained that a similar concept could be applied to hexose disaccharide lithium adducts.…”
Section: Resultsmentioning
confidence: 96%
“…A LODES for CID tandem MS was developed based on the understanding of the dissociation mechanisms of carbohydrate sodium adducts . This sequence can be used for generating the chosen mono‐ and disaccharides for subsequent structural determination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 In the present study, the CID spectrum of each disaccharide anomer was measured immediately after the separation of anomers by HPLC. Our previous study 44,45 on hexose disaccharide sodium adducts demonstrated that both the anomeric configurations of the glycosidic bond and the sugar at the reducing end can be determined using the relative intensities of glycosidic bond cleavage, dehydration, and cross-ring dissociation. We ascertained that a similar concept can be applied to hexose disaccharide lithium adducts.…”
Section: Identifications Of Linkagesmentioning
confidence: 99%
“…Reducing end is located at the monosaccharide unit 1. The colors used in this figure are simply to distinguish different types of trisaccharides, they are not related to the color codes used in the symbol nomenclature of Consortium for Functional Glycomics (CFG).Logically derived sequences (LODES) for MSn logically derived sequence (LODES) for CID tandem mass spectrometry was developed based on the understanding of the dissociation mechanisms of carbohydrate sodium adducts44,45…”
mentioning
confidence: 99%